Electronic Structures of Eu-Doped FAPbI3 Perovskite Crystals Studied by First-Principles Calculation - Atsushi Suzuki; Takeo Oku (Chemistry Proceedings, 2022)
The effects of maxed-valence states on electronic structures of europium (Eu)-incorporated CH(NH2)2PbI3 (FAPbI3) and CH3NH3PbI3 (MAPbI3) perovskite crystals were investigated by first-principles calculation. Partial replacements of europium ions into the perovskite crystals influenced the electronic structures. In the case of the FAPb(Eu+3)I3 crystal, there was wide distribution of the 5p orbital of iodine near the valence band, and of the 3d orbital of the Eu3+ ion near the conductive band. Incorporation of Eu2+ ions into the perovskite crystal provided low energy levels at the VB, with an increase in the bandgap and a decrease in mh*/me. This behaviour suggests improvement of carrier mobility related to short-circuit current and conversion efficiency, as compared with the incorporation of Eu3+ ions into the perovskite crystal. The partial substitution of europium ions at the position of lead ions as the B-site in the perovskite crystal caused the electron correlation based on the charge transfer between the 5p orbital of iodine and the 3d orbital of Eu ions, and narrowed the band dispersion with a decrease in the effective mass ratio, which was expected to improve the carrier mobility related to the short-circuit current density and the conversion efficiency.